Quantity Over Quality? Reproducible Psychological Science from a Mixed Methods Perspective - Hollen N. Reischer; Henry R. Cowan (Collabra: Psychology, 2020)
A robust dialogue about the (un)reliability of psychological science findings has emerged in recent years. In response, metascience researchers have developed innovative tools to increase rigor, transparency, and reproducibility, stimulating rapid improvement and adoption of open science practices. However, existing reproducibility guidelines are geared toward purely quantitative study designs. This leaves some ambiguity as to how such guidelines should be implemented in mixed methods (MM) studies, which combine quantitative and qualitative research. Drawing on extant literature, our own experiences, and feedback from 79 self-identified MM researchers, the current paper addresses two main questions: (a) how and to what extent do existing reproducibility guidelines apply to MM study designs; and (b) can existing reproducibility guidelines be improved by incorporating best practices from qualitative research and epistemology? In answer, we offer 10 key recommendations for use within and outside of MM research. Finally, we argue that good science and good ethical practice are mutually reinforcing and lead to meaningful, credible science.